Educationally adaptive: Balancing serious games - Kickmeier-Rust, M. D.; Albert, D. (International Journal of Computer Science in Sport, 2012)
A key factor for the success and efficacy of an educational medium is the extent to which it is capable of addressing the preferences, abilities, strengths, weaknesses, and goals of individual learners. Research in the field of learning and instruction has demonstrated in the past that one on one tutoring is the most effective and powerful way of teaching. Ever since, the research community attempted to equip artificial systems with the strength and abilities of human tutors. Specifically in a medium such as educational computer games an appropriate personalization is a key factor for fun, immersion, and ultimately learning. The same holds true for serious, in particular educational, games. Because the key strength of serious games is seen in their intrinsic motivational potential, it`s all about focusing on the learners. More importantly, in contrast to conventional educational systems, in games this means accounting for both, a game related and a learning related hemisphere. This report attempts to emphasize the importance of advancing a construct such "educational game AI" and it illustrates recent technologies and approaches.